Self-Assembly of Black Cumin Oil-Based Nanoemulsion on Various Surfactants: A Molecular Dynamics Study - Hidayat, Aulia Fikri; Fakih, Taufik Muhammad (Makara Journal of Science, 2021)
Black cumin is commonly used as traditional medicine due to its wide range of pharmacological potential. Black cumin oil (BCO) was often prepared as nanoemulsion to improve its solubility, stability, and bioavailability. This study was conducted to investigate the molecular behavior as well as structural evolution of BCO-surfactant systems during self-assembly micellization using molecular dynamics (MD) simulations. Several BCO constituents and variations of surfactants were employed to model BCO-surfactant systems. 50 ns of MD simulations were performed to elucidate their evolution of structures and physicochemical properties during formation. Results showed that BCO-tween20 and BCO-lecithin were able to form spherical-shaped micelles with the effective radii of 10.20 and 8.67 nm at the end of the simulation. Also, from the root mean square deviation and radius of gyration profile, it is showed that BCO-tween20 system was able to maintain the stability of its structure throughout the simulation. Results also revealed that self-assembly of BCO-surfactant systems were exothermic processes, confirming spontaneous nature upon formation